Generation of methane in the Earth's mantle: In situ high pressure–temperature measurements of carbonate reduction - Scott, Henry P. (National Academy of Sciences, 2004)
We present in situ observations of hydrocarbon formation via carbonate reduction at upper mantle pressures and temperatures. Methane was formed from FeO, CaCO(3)-calcite, and water at pressures between 5 and 11 GPa and temperatures ranging from 500°C to 1,500°C. The results are shown to be consistent with multiphase thermodynamic calculations based on the statistical mechanics of soft particle mixtures. The study demonstrates the existence of abiogenic pathways for the formation of hydrocarbons in the Earth's interior and suggests that the hydrocarbon budget of the bulk Earth may be larger than conventionally assumed.